Learning strategies used by high achiever student's of smp n 1 dolopo in developing english - Supriyanto, Agus; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriyah Ariatmi, M. Hum (2014)
The research studies about learning strategies used to develop the four skills of English; Listening, Speaking, Reading, and Writing skills on high achiever students of SMPN 1 Dolopo. The type of this research is qualitative research which aims at describing the subjects' learning strategies in developing the four English skills. The subjects of this research are three students chosen based on the English class. The method of collecting the data are interview, observation and documentation. The result of this research shows that the three of the subjects uses almost all of the learning strategies proposed by O'Malley and Chamot. However their action and attention in learning english are different. S1 uses 12 learning strategies which consists of 5 metacognitive strategies; advance organizer, directive attention, selective attention, self-management, selfevaluation, 5 cognitive strategies which consists of repetition, resourcing, imagery, ealboration, and note taking, and one socio-affective strategy that is question for clarification. S2 uses 11 learning strategies which consists of 5 metacognitive strategies which consists of repetition, resourcing, directed attention, selective attention, self-management, self monitoring, note taking, and self evaluation. S3 uses 9 learning strategies which consists of 3 metacognitive strategies; advance organizer, selective attention, self management, 4 cognitive strategies which consists of repetition, resourcing, imagery, elaboration, and two socio affective strategies which consists of repetition, resourcing, imagery, elaboration, and two socio affective strategies those are cooperation and question for clarification. Based on the result of this research, the researcher concludes that all of the learning strategies used by the subjects are effective strategies which are important to improve the learners' the four English skills. Some learning strategies which are important to improve the learners' English skill are: advance organizer, selective attention, self management, repetition, resourcing, and elaboration.